GOOD GOVERNANCE: A KEY TO ENHANCE AGRICULTURAL GROWTH IN INDIA - Patel, Amrit (International Journal of Research -GRANTHAALAYAH, 2016)
For India agricultural growth rate of minimum 4 percent per annum is a must to ensure livelihood of 48.9 percent population engaged in agriculture, food and nutritional security of country’s rising population and last but not the least to alleviate rural poverty. Since country’s Independence in 1947 and from the first five year plan to twelfth five year plan, the Government has initiated policy and formulated innumerable programs to accelerate the agricultural growth rate. However, not only the share of agriculture in India’s GDP progressively declined from 23.4% in the 9th five year plan[1997-02] to 17.60% in 2014-15 but also the agricultural growth rate during 2014-15 is abysmally the lowest at 0.2 percent as against country’s 7.3 percent economic growth rate. Food output in 2014-15 is estimated to be 251.12 million tons [MT] significantly less than 257.13 MT and 265.14 MT in 2012-13 and 2013-14 respectively. This, therefore, points to the focused need for good governance in agriculture right from the concern and commitment of policy-makers through transparent and farmer-friendly administration and implementation of agricultural development programs to the accountability to the farmers to achieve the targeted growth rate and development of agriculture. It is in this context, this development perspective article highlights critical components of good governance in agriculture.